PERANAN MOTIVASI DALAM MENINGKATKAN PRODUKTIVITAS KERJA PEGAWAI PADA KANTOR KELURAHAN KARANG ANYAR KECAMATAN TANJUNG PALAS KABUPATEN BULUNGAN - Syaini, Syaini; Masruri, Masruri (JISOS: JURNAL ILMU SOSIAL, 2023)
This Research aim to to know and/or description role of motivation in improving officer work productivity Office Sub-District Of Rock of Anyar District Of Foreland of Palas Sub-Province of Bulungan. Type Research which is used in this research if evaluated according to used method hence including research type qualitative. While research data analysis use analysis of interaktif which consist of three step analyse that is : data discount, presentation of data, and withdrawal of conclusion / verification. Pursuant to result of analysis and research which is known that motivation work important so central in improving officer work productivity at Office Sub-District Of Rock of Anyar District Of Foreland of Palas Sub-Province of Bulungan. Type Motivation job/activity applied by Head Sub-District Of Rock of Anyar District Of Foreland of Palas Sub-Province of Bulungan to all its officer is positive motivation type which is dikasifikasikan become material of incentive and of nonmaterial incentive